Benin : 2017 Article IV Consultation and First Review Under the Extended Credit Facility Arrangement and Request for Modifications of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that Benin has shown mixed macroeconomic performance in 2016, with the economy weathering negative spillover stemming from a difficult external environment. Growth was about 4 percent, but a recovery is expected in 2017-18, owing to strong agricultural production, an increase in public investment, and a buoyant tertiary sector. Economic growth is accelerating and inflation remained negative in 2016 and through end-August 2017 but is forecasted to average 0.6 percent in 2017. The medium-term outlook continues to show favorable signs, with high economic growth and low inflation. Cuts in recurrent spending have contributed to a smaller than programmed budget deficit of 6.0 percent of GDP in 2016 from 8.0 percent in 2015.